PENGARUH PERENCANAAN PAJAK DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Lestari, Dea Safitri Ayu; Kurnia, Ia; Yuniati, Yuniati (2018)
This research was conducted to see the effect of tax planning and company size on earnings management (Empirical Study on Company MAnufacturing Listed In Indonesia Stock Exchange). The factors tested in this study are tax planning and company size as independent variables and earnings management as the dependent variable. This type of research is descriptive method of analysis and type of research is quantitative research. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange during the period 2015-2017. Sampling technique in this study using purposive sampling technique, so that obtained the number of samples of 21 companies with the final data amounted to 63 financial statements. Sources of data in this study are secondary data downloaded through www.idx.co.id and corporate website each in the form of annual financial statements of the company for 3 years in the period 2015 to 2017. Data analysis techniques in this study using multiple linear regression analysis. The results of this study indicate that simultaneously tax planning and the size of the company have a significant influence on the earings management in manufacturing companies listed on the Indonesia Stock sExchange for the 2015-2017 period.